Testing the limits of resistance: a 19‐year study of Mediterranean grassland response to grazing regimes. (18th February 2015) - Sternberg, Marcelo; Golodets, Carly; Gutman, Mario; Perevolotsky, Avi; Ungar, Eugene D.; Kigel, Jaime; Henkin, Zalmen
Abstract: A synthesis of a long‐term (19 years) study assessing the effects of cattle grazing on the structure and composition of a Mediterranean grassland in north‐eastern Israel is presented, with new insights into the response of the vegetation to grazing management and rainfall. We hypothesized that the plant community studied would be resistant to high grazing intensities and rainfall variability considering the combined long history of land‐use and unpredictable climatic conditions where this community evolved. Treatments included manipulations of stocking densities (moderate, heavy, and very heavy) and of grazing regimes (continuous vs. seasonal), in a factorial design. The effect of interannual rainfall variation on the expression of grazing impacts on the plant community was minor. The main effects of grazing on relative cover of plant functional groups were related to early vs. late seasonal grazing. Species diversity and equitability were remarkably stable across all grazing treatments. A reduction in tall grass cover at higher stocking densities was correlated with increased cover of less palatable groups such as annual and perennial thistles, as well as shorter and prostrate groups such as short annual grasses. This long‐term study shows that interannual fluctuations in plant functional group composition could be partly accounted for by grazing pressure and timing, but not by the measured rainfall variables. Grazing affected the dominance of tall annual grasses. However, the persistence of tall grasses and more palatable species over time, despite large differences in grazing pressure and timing, supports the idea that Mediterranean grasslands are highly resistant to prolonged grazing. Indeed, even under the most extreme grazing conditions applied, there were no signs of deterioration or collapse of the ecosystem. This high resistance to grazing intensity and interannual fluctuation in climatic conditions should favor the persistence of the plant community under forecasted increasing unpredictability due to climate change.